Building Fault Tollrence within Clouds at Network Level - Sastry Kodanda Rama Jammalamadaka; Kamesh Bala Krishna Duvvuri; Devi Anusha CH; Padmini P; Siva Anjaneyulu G (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Cloud computing technologies and infrastructure facilities are coming up in a big way making it cost effective for the users to implement their IT based solutions to run business in most cost-effective and economical way. Many intricate issues however, have cropped-up which must be addressed to be able to use clouds the purpose for which they are designed and implemented. Among all, fault tolerance and securing the data stored on the clouds takes most of the importance. Continuous availability of the services is dependent on many factors. Faults bound to happen within a network, software, and platform or within the infrastructure which are all used for establishing the cloud. The network that connects various servers, devices, peripherals etc., have to be fault tolerant to start-with so that intended and un-interrupted services to the user can be made available. A novel network design method that leads to achieve high availability of the network and thereby the cloud itself has been presented in this paper